2009
DOI: 10.1086/597772
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium prolificansOsteomyelitis in an Immunocompetent Child Treated with a Novel Agent, Hexadecylphospocholine (Miltefosine), in Combination with Terbinafine and Voriconazole: A Case Report

Abstract: We describe an 8-year-old girl who sustained multiple compound fractures in an accident involving agricultural equipment. She developed Scedosporium prolificans osteomyelitis of the pelvis, septic arthritis of the hip, and myositis of adjacent muscles. The infection progressed, despite extensive surgical debridement and joint washouts with 0.2% polyhexamethylene biguanide; antifungal therapy with caspofungin, terbinafine, and voriconazole; and adjunctive therapy with interferon-gamma. Gradual resolution was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 15 publications
0
50
0
2
Order By: Relevance
“…There are relatively few case reports of isolated osteoarticular infections due to dematiaceous fungi, perhaps reflecting the significant trauma often required for implantation into these deeper tissues, though some cases did not have noticeable trauma. S. prolificans is the most common cause, with all except two cases occurring in young children (166,299,325,406,453,474,716,718). In addition to surgery, various antifungal therapies have been employed, with three cases using the combination of voriconazole and terbinafine with success (166,299,406).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…There are relatively few case reports of isolated osteoarticular infections due to dematiaceous fungi, perhaps reflecting the significant trauma often required for implantation into these deeper tissues, though some cases did not have noticeable trauma. S. prolificans is the most common cause, with all except two cases occurring in young children (166,299,325,406,453,474,716,718). In addition to surgery, various antifungal therapies have been employed, with three cases using the combination of voriconazole and terbinafine with success (166,299,406).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…S. prolificans is the most common cause, with all except two cases occurring in young children (166,299,325,406,453,474,716,718). In addition to surgery, various antifungal therapies have been employed, with three cases using the combination of voriconazole and terbinafine with success (166,299,406). Unusual therapies have also been tried, including irrigation with polyhexamethylbiguanide and oral therapy with miltefosine (406,716).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…The in vitro study of 35 antifungal combinations against S. apiospermum and S. prolificans describing a potent synergy between azole drugs and echinocandins will probably reopen the debate on combination therapy (8,23). Promising results obtained with new antifungal agents such as miltefosine remain to be confirmed (20,30). In the present case, it is interesting to note the reliability of the Etest for MIC determination for Scedosporium species, as MICs obtained by the Etest were generally correlated with those obtained by the EUCAST method, especially for voriconazole.…”
Section: Vol 48 2010mentioning
confidence: 99%
“…In addition, more recently, it has been shown to have fungicidal activity against Scedosporium, Fusarium, and Mucormycetes. [18][19][20] In vitro studies have shown that miltefosine demonstrates synergistic interactions when combined with posaconazole or voriconazole against a series of uncommon filamentous fungi [20] and can also cause a significant reduction in amphotericin B and voriconazole minimum inhibitory concentrations when used against Scedosporium spp. [21] In vivo, miltefosine given orally to mice after intravenous infection with C. neoformans delayed the morbidity and mortality and reduced the cryptococcal burden in the brain.…”
Section: Repurposing Of Approved Drugs Against Human Fungal Pathogensmentioning
confidence: 99%